PENGARUH METODE MASSAGE TERHADAP PENGURANGAN INTENSITAS NYERI PADA PERSALINAN KALA I - AS, Emilda; Elfida, Elfida; Fazdria, Fazdria (Poltekkes Kemenkes Yogyakarta, 2014)
Pain during labor is a thing that makes women feel anxious .Assume that pain is a physiological process that even the other type of pain that is always caused by an accident or illness , Massage is one of the non-pharmacologicalmethods are done to relieve labor pain. Objective: To determine the effect of method of Massage Pain Intensity Reduction In the first stage of labor in the Delivery RoomGeneral Hospital Aceh Tamiang